TP6.2.20 UK- single centre experience with the ElipseTM intragastric balloon; Early safety and effectiveness. (28th October 2021) - Oyewole, Bankole; Stefanova, Irena; Sandhya, Anu; Mangat, Shannon; Monkhouse, Simon
Abstract: Introduction: The Elipse TM gastric balloon (EIGB) is an established outpatient, non-invasive, non-surgical device for weight-loss not requiring endoscopy nor sedation. This study reports the early safety and effectiveness from the largest and only reported UK cohort treated with the EIGB. Methods: A retrospective study of 224 consecutive patients undergoing EIGB insertion between May 2018 and December 2020 was performed. EIGB placement involved swallowing of the Elipse TM capsule followed by a pre-inflation abdominal radiograph to confirm position. Inflation was performed with 550mls of sterile water followed by a post-inflation radiograph. Patients had weekly follow-up to assess symptoms, weight-loss, time and route of balloon expulsion. Results: 224 patients underwent EIGB insertion during the study period; 39 patients were lost to follow-up. 185 patients (28 male and 157 female) were included in the final analysis with a mean age of 38.1 years. Mean study follow-up was 10 weeks, mean weight at insertion was 97.7 kg. Mean %Total Body Weight (TBW) loss was 6.5% at 4 weeks and 9% at last follow-up. 32 patients had 15.3 %TBW loss at 16 weeks follow-up. Frequently experienced symptoms during the first week were acid reflux, abdominal pain and bloating, nausea and vomiting. One patient had early expulsion at 8 weeks. Seven patients required early deflation due to severe symptoms (5), pancreatitis (1) and hyperinflation (1). Conclusion: EIGB is a safe and effective method of weight loss. Longer follow-up studies in the UK population are required to assess overall patient outcomes and associated factors for weight loss.